2008
DOI: 10.1103/physrevlett.100.252301
|View full text |Cite
|
Sign up to set email alerts
|

Fast Equilibration of Hadrons in an Expanding Fireball

Abstract: Due to long chemical equilibration times within standard hadronic reactions during the hadron gas phase in relativistic heavy ion collisions it has been suggested that the hadrons are "born" into equilibrium after the quark gluon plasma phase. Here we develop a dynamical scheme in which possible Hagedorn states contribute to fast chemical equilibration times of baryon anti-baryon pairs (as well as kaon anti-kaon pairs) inside a hadron gas and just below the critical temperature. Within this scheme, we use mast… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 33 publications
5
89
0
Order By: Relevance
“…On the other hand, an exponentially increasing density of state was necessary to explain the rapid increase in entropy density near the transition region in lattice QCD simulation [31]. Such exponential rise of density of states has also been used to study observables like dilepton production [32] as well as chemical equilibration [33]. Motivated by such observations we take the modified spectral function as [18,34,35] …”
Section: Hadron Resonance Gas Modelmentioning
confidence: 99%
“…On the other hand, an exponentially increasing density of state was necessary to explain the rapid increase in entropy density near the transition region in lattice QCD simulation [31]. Such exponential rise of density of states has also been used to study observables like dilepton production [32] as well as chemical equilibration [33]. Motivated by such observations we take the modified spectral function as [18,34,35] …”
Section: Hadron Resonance Gas Modelmentioning
confidence: 99%
“…When T < 100 MeV, the discreteness of the hadron spectrum becomes relevant and the continuous approximation discussed here gives a poor description of the thermodynamic quantities of a hadron resonance gas. Therefore, to have a hadronic equation of state that is valid at both low temperatures (T < 100 MeV) and higher temperatures a hybrid model containing the measured hadron states plus a continuous Hagedorn spectrum above a certain mass cutoff is more appropriate [16][17][18][19][20].…”
Section: Hadron Mass Spectrum and The Hadron Resonance Gas Modelmentioning
confidence: 99%
“…[13] that a small value of η/s in QCD should occur in the transition region T ∼ 150-200 MeV owing to the rapid increase in the entropy density observed in lattice simulations [14,15], the effects of an exponentially increasing density of hadronic states on several properties of hot hadronic matter were investigated using the hadron resonance gas model in Refs. [16][17][18][19][20]. It was shown in those studies that the addition of new hadronic states that follow an exponentially increasing hadron mass spectrum as proposed by Hagedorn [21], …”
Section: Introductionmentioning
confidence: 99%
“…[48]) that this could explain the tension, as decays of high mass resonances would affect pions more than protons. Quantitative calculations were made in [49,50,51], where it was shown that reasonable assumptions on high mass resonances based on the Hagedorn spectrum could explain the low p/π. However, these additional states could potentially spoil the agreement with other particle ratios (most notably, multistrange baryons, which could however be included as discussed [52]) and some of the underlying assumptions of the model are not constrained by first principles.…”
Section: Heavy Ion Collisions At High Energymentioning
confidence: 99%